Revisiting the Nexus between Climate Change and Unemployment in South Africa - Adekunle, Ahmed Oluwatobi (Acta Universitatis Danubius. Œconomica, 2024)
Emancipating policy coherence and achieve a sustainable future, it is essential to identify the linkages between the 17 Sustainable Development Goals (SDGs) put out by the UN. Sequel to this, the study revisits the nexus between climate change and unemployment in South Africa. The study employed time series data span through 1986-2021. The ARDL econometric techniques is used to evaluates the nexus amid the variables. Given that the long-term coefficient of climate change (Tpr) is positive and statistically significant at the 5% level, the long-run result support the expected sign that climate change has a positive impact on unemployment in South Africa. The government of South Africa need thus concentrate more on lowering the country’s inflation rate and strengthening the local currency relative to the US dollar. In the meantime, the shortage of jobs in South Africa will worsen due to the rise in unemployment brought on by the rising temperatures. Here, the government should increase funding at the federal level for a number of industries, including forestry, tourism, agriculture, and fisheries, that are heavily reliant on climate change.